The Current Issue of Reporting Zakat in Indonesia: A Critical Analysis - Mohammad Qutaiba; Mohd Owais; Abdus Salam Muharam (Journal of Islamic Economic and Business Research, 2024)
The functions of zakat collection and distribution in Indonesia are carried out by both government and private institutions. Zakat funds hold significant economic development potential. Despite rapid growth in the past decade, the true potential of zakat remains largely untapped. Various factors contribute to suboptimal zakat management in Indonesia, such as ineffective zakat collection organizations, high administrative costs, and ineffective dissemination of information on the importance of zakat payment. This study focuses on the governance of zakat institutions in Indonesia, with a primary emphasis on the National Amil Zakat Agency (BAZNAS) and authorized Private Zakat Institutions (LAZ). This paper is based on a descriptive-analytical method, and it adopts qualitative research for the analysis of the available literature. The research is crucial for building trust, ensuring efficient zakat utilization for poverty alleviation, and enhancing social welfare within the Indonesian context. This research delves into the governance of zakat institutions in Indonesia, primarily focusing on the National Amil Zakat Agency (BAZNAS) (Zakat Institution of the Republic of Indonesia) and authorised Amil Zakat Institutions (LAZ) LAZ (Private Zakat Institutions). Despite official recognition, a lingering lack of trust among some members of the Muslim community necessitates a closer examination of transparency and accountability in zakat collection and distribution. The study aims to assess the reporting practices of zakat institutions, identifying areas for improvement to bolster confidence in the Muslim community. The research holds significance in fostering trust, ensuring effective zakat utilisation for poverty alleviation, and promoting social welfare.